الرضا الوظيفي للعاملين في مجال الإدارة الرياضية في اللجنة التنفيذية لفرعي اللاذقية وطرطوس(2017/2018) - معوض, وائل; علي, محمد; جراد, يامن (Latakia University Journal -Medical Sciences Series, 2018)
Job satisfaction is one of the most important indicators of success in an organization or institutions. Job satisfaction represents the total positive feelings and attitudes of staff towards work that reflects their commitment to disciplined and positive performance. The study aimed to identify: Degree of job satisfaction for the employees of the Executive Committee of the General Federation of Sport in Lattakia and Tartous to determine the differences between the employees in the job satisfaction according to the variable (nature of work, gender and experience). The researcher used the descriptive method in a comparative manner on a sample of (97) individuals (70.80%) of the total research community. The researcher used a trail scale to measure the degree of job satisfaction. The study found that there is no difference in the degree of job satisfaction among the employees in sports administration in Lattakia and Tartous. There is no significant difference in the degree of job satisfaction for each of the variables (nature of work - experience). There were statistically significant differences in the degree of satisfaction in the variable (gender) in favor of males. يعد الرضا الوظيفي للفرد العامل من أهم مؤشرات النجاح في المنظمة أو المؤسسة ، حيث يمثل الرضا الوظيفي مجموع المشاعر والاتجاهات الايجابية التي يبديها العاملين نحو العمل والتي تعبر عن التزامهم بالأداء المنضبط والإيجابي ,هدفت الدراسة إلى التعرف على : درجة الرضا الوظيفي لدى العاملين في اللجنة التنفيذية للاتحاد الرياضي العام في اللاذقية وطرطوس, التعرف على الفروق بين العاملين في الرضا الوظيفي تبعاً لمتغير (طبيعة العمل ,الجنس, الخبرة) . استخدم الباحث المنهج الوصفي بأسلوب المقارنة على عينة قوامها (97) فردا بنسبة ( 70.80%) من مجتمع البحث الكلي , واستخدم الباحث مقياس دارب لقياس درجات الرضا الوظيفي , وتوصلت الدراسة إلى عدم وجود اختلاف بدرجات الرضا الوظيفي بين العاملين في مجال الإدارة الرياضية في اللجنة التنفيذية للاتحاد الرياضي العام في اللاذقية وطرطوس وتقاربت درجات الرضا الوظيفي لدى الفرعين بشكل غام وجميعها تقع في المستوى المتوسط ,ولا يوجد فروق معنوية بدرجات الرضا الوظيفي لكل من متغيري (طبيعة العمل – الخبرة ) ,فيما كانت هناك فروق ذات دلالة احصائية بدرجة الرضا في متغير (الجنس ) ولصالح الذكور .